Acesso aos profissionais de reabilitação por indivíduos pós acidente vascular cerebral após um, três e seis meses da alta hospitalar - Jordana de Paula Magalhães (2022)
To increase the chances of recovery, it is recommended that post-stroke individuals have access to rehabilitation professionals after hospital discharge and that access should be continued until their functional goals are achieved. Therefore, immediate, comprehensive, and continuous access to rehabilitation professionals after hospital discharge is essential. Despite these recommendations, previous studies have shown difficulties in accessing rehabilitation professionals by individuals with stroke in different countries around the world. However, the determinants of access during the first six months after hospital discharge are not known. In addition, studies comparing access to rehabilitation professionals by individuals with stroke before and during the Corona Virus Disease (COVID-19) pandemic were not found. Therefore, two studies were developed in this dissertation. Study 1, aimed at comparing access to rehabilitation professionals by individuals with stroke one month after hospital discharge, before and during the COVID-19 pandemic, in Brazil. A total of 146 individuals (divided into two groups) were included: G1: hospital admission before the pandemic and G2: hospital admission during the pandemic. Access to rehabilitation professionals was similar between the groups. However, the number of accessed professionals was significantly lower than that referred (p<0.001). Therefore, the COVID-19 pandemic did not impact access to rehabilitation professionals by individuals with stroke one month after hospital discharge in Brazil. However, in both periods, access was significantly lower than that was recommended, compromising the comprehensiveness of care for individuals with stroke. Study 2, aimed at identifying the determinants of access to rehabilitation professionals by individuals with stroke after one, three, and six months of hospital discharge, in Brazil and to compare the obtained access in each period with that recommended at the time of hospital discharge. The study was based on Andersen's behavioral model on determinants of health service utilization. Two-hundred and one individuals were included. Disability levels and stroke severity explained 31%, 34% and 39% of access to rehabilitation professionals one, three and six months after hospital discharge. Three months after discharge, educational levels added a 4% explanation of access variance. In all evaluated periods, the number of professionals accessed was significantly lower than recommended (p<0.01). Therefore, higher levels of disability and stroke severity were determinants of access to rehabilitation professionals in all evaluated periods. Three months after discharge, was directed to individuals who, in addition to have greater clinical-functional needs, had lower education levels. In addition, in all periods, the integrality of care was compromised. The results of this dissertation will be useful for the knowledge of access to rehabilitation professionals by individuals with stroke during different health contexts. In addition, these results may be useful for health management services to understand the direction of access to rehabilitation professionals and to plan public policies aimed at improving the effectiveness of transferring hospital care to community care for individuals with stroke.